ПОТОМКИ ЧИНГИЗХАНА И РУССКОЕ ДВОРЯНСКОЕ СОСЛОВИЕ: ПОЛИИДЕНТИЧНОСТЬ КАЗАХСКОЙ ЭЛИТЫ В УСЛОВИЯХ ИМПЕРСКОГО ПРАВЛЕНИЯ - Tuleshova, U. (Journal of history, 2023)
It seems imperial biographies are significant aspects of researching the social history of empires, and the biographical approach to historical study increases if it draws real social pictures in borderlands. In researching Kazakh elite biographies within imperial time, it is crucial to study the influence of the epoch on the formation of personality and consider the features of sociocultural context. In this research, we focus on multiple identities of the Kazakh traditional elite, who, by changing the subject, tried to save advantageous positions on both sides: in imperial society and among Kazakh nomads. The paper's main argument is that Kazakh sultans, descendants of Chengizkhan, could successfully adapt to new imperial administrative and social order, accepting multiple identities, saving "sultan" status, and gaining privileged estate positions. Moreover, we propose to demonstrate that Kazakh sultans identified themselves as aristocratic strata of Kazakh nomadic people, serving to Kazakh people, governing them, and at the same time, taking into account their noble title and high position in the imperial social structure. To better understand such a dynamic, this paper considers the example of Kazakh noble branches of the great Kazakh sultan family, particularly the Ualikhanovs. This paper aims to explore the formation and character of the multi-identity of Kazakh traditional aristocracy, the process and way of adapting to new orders in biographical and social history methodological perspectives.